The Resistance of Madurese Muslim Society to the Development of Non-Muslim Tourism Objects - Hariyanto, Erie; Cahyani, Novita; Susylawati, Eka; Long, Ahmad Sunawari; Qudsy, Saifuddin Zuhri; Supraptiningsih, Umi (SCAD Independent, 2024)
Madurese’s resistance to the development of tourism facilities is based on the socio-cultural conditions of the community, which is less open to modernization. This research describes the form of resistance and reflects on its relation to Madurese society’s social and historical conditions. This research uses qualitative data with interview methods, collecting news on the internet, and literature studies. Data collection in this research begins with reading news on the internet on Madurese's resistance related to modern facilities and modern tourism, then conducting interviews with informants to confirm data from the news. Data analysis was carried out through three stages, namely describing data, classifying, and interpreting data thematically to reveal the meaning of the resistance by the Madurese community against the development of tourism facilities. The findings of this study highlight at least three main things, namely the forced closure of non-Muslim entertainment venues due to dissatisfaction with the resulting value shifts. Second, the presence of powerful actors triggers resistance from the community. Third, Madurese people tend to make tourism based on Islamic Sharia as they believe in their daily lives.